Пошаговое объяснение:
1)
Y=cos(6x-9)
Y'=(cos(6x-9))'×(6x-9)'=-6sin(6x-9)
Y=sin(7x^6+5x-8)
Y'=(sin(7x^6+5x-8))'×(7x^6+5x-8)' = cos(7x^6+5x-8)×(42x^5+5)
Y=tg(3x^3+1)
Y'=(9x^2)/cos^2(3x^3+1)
2)
Y=ln(4x-3)
Y'=4/(4x-3)
Y=ln(2x^5+4x+3)
Y'=(10x^4+4)/(2x^5+4x+3)
Y=log5(2x^3+4)
Y'=6х^2/((2х^3+4)×ln5)
3)
Y=e^(3x-5)
Y'=3×e^(3x-5)
Y=4e^-5x
Y'=-20e^-5x
Y=6^(4x+1)
Y'=6^(4x+1)×ln6
4)извини, но дальше мне лень печатать:с
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Пошаговое объяснение:
1)
Y=cos(6x-9)
Y'=(cos(6x-9))'×(6x-9)'=-6sin(6x-9)
Y=sin(7x^6+5x-8)
Y'=(sin(7x^6+5x-8))'×(7x^6+5x-8)' = cos(7x^6+5x-8)×(42x^5+5)
Y=tg(3x^3+1)
Y'=(9x^2)/cos^2(3x^3+1)
2)
Y=ln(4x-3)
Y'=4/(4x-3)
Y=ln(2x^5+4x+3)
Y'=(10x^4+4)/(2x^5+4x+3)
Y=log5(2x^3+4)
Y'=6х^2/((2х^3+4)×ln5)
3)
Y=e^(3x-5)
Y'=3×e^(3x-5)
Y=4e^-5x
Y'=-20e^-5x
Y=6^(4x+1)
Y'=6^(4x+1)×ln6
4)извини, но дальше мне лень печатать:с